The Jekyll and Hyde story of IL17 producing γδT (Tγδ17) cells - Patil, Rushikesh S.; Bhat, Sajad A.; Dar, Asif A.; Chiplunkar, Shubhada V. (Frontiers in Immunology, 2015)
In comparison to conventional αβT cells, γδT cells are considered as specialized T cells based on their contributions in regulating immune response. γδT cells sense early environmental signals and initiate local immunosurveillance. The development of functional subtypes of γδT cells takes place in the thymus but they also exhibit plasticity in response to the activating signals and cytokines encountered in the extrathymic region. Thymic development of Tγδ1 requires strong TCR, CD27 and Skint1 signals. However differentiation of IL17 producing γδT cells (Tγδ17) is independent of Skint1 or CD27 but requires notch signalling along with IL6 and TGFβ cytokines in the presence of weak TCR signal. In response to cytokines like IL23, IL6 and IL1β, Tγδ17 outshine Th17 cells for early activation and IL17 secretion. Despite expressing similar repertoire of lineage transcriptional factors, cytokines and chemokine receptors, Tγδ17 cells differ from Th17 in spatial and temporal fashion. There are compelling reasons to consider significant role of Tγδ17 cells in regulating inflammation and thereby disease outcome. Tγδ17 cells regulate mobilization of innate immune cells and induce keratinocytes to secrete antimicrobial peptides thus exhibiting protective functions in antimicrobial immunity. In contrast, dysregulated Tγδ17 cells inhibit Treg cells and exacerbate autoimmunity and are also known to support carcinogenesis by enhancing angiogenesis. The mechanism associated with this dual behaviour of Tγδ17 is not clear. To exploit Tγδ17 cells for beneficial use requires comprehensive analysis of their biology. Here we summarize the current understanding of the characteristics, development and functions of Tγδ17 cells in various pathological scenarios.